1970
DOI: 10.3329/bja.v7i1.3010
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurements of the hand length and their correlation with the Stature of Bengali adult Muslim females

Abstract: Context: Stature or body height is one of the most important and useful anthropometric parameter that determine the physical identity of an individual. The study was done to estimate stature from the hand length on one hundred and fifty Bengali adult Muslim females. Study design: descriptive cross sectional study. Place of Study: department of Anatomy, BSMMU, Dhaka. Material: One hundred and fifty Bengali adult Muslim female was collected from BSMMU & some urban region of Dhaka. Method: Measurement of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
3

Year Published

1970
1970
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
12
3
Order By: Relevance
“…It should be noted that the highest mean stature was found in the Negroid adult females like the Somali in Ethiopia 1 .The mean length of right hand was 16.39 and left hand was 16.33 centimetres and the average value was 16.36 centimetres in the present study. Similar value was reported in Bengali adult females 12 . Higher value was also found in Punjabi females 17 , Mangalore females and other Indian females 18 , while Nigerian females 20 belong to Negroid race, showed higher value.In the present study, the mean breadth of right hand was 7.22 and left hand was 7.18 centimetres.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It should be noted that the highest mean stature was found in the Negroid adult females like the Somali in Ethiopia 1 .The mean length of right hand was 16.39 and left hand was 16.33 centimetres and the average value was 16.36 centimetres in the present study. Similar value was reported in Bengali adult females 12 . Higher value was also found in Punjabi females 17 , Mangalore females and other Indian females 18 , while Nigerian females 20 belong to Negroid race, showed higher value.In the present study, the mean breadth of right hand was 7.22 and left hand was 7.18 centimetres.…”
Section: Discussionsupporting
confidence: 90%
“…Higher value was also found in Punjabi females 17 , Mangalore females and other Indian females 18 , while Nigerian females 20 belong to Negroid race, showed higher value.In the present study, the mean breadth of right hand was 7.22 and left hand was 7.18 centimetres. Average value was 7.20 centimetres .Smaller value was reported in Bengali adult females 12 and in Indian females 18 . Higher value was only found in Nigerian females 19 of Negroid race and in Turks 20 females of Caucasoid race.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A study on Malaysian females showed mean arm-span nearer to this value of the Chakma females 11 . If we see the other ethnic groups such as Urban Bengali females, South and North Indians females 12,13 of India and Asians studying in Oxford Brooks University 10 , we have found that all of them considered in this study showed higher value than this. In the present study, the mean stature of the Chakma females was found as148.74± 5.34 centimeters.…”
Section: Resultsmentioning
confidence: 53%
“…Hand and foot parameters have long been used for determination of stature [13][14][15][16]. Studies have shown that hand dimensions vary in different races.…”
Section: Discussionmentioning
confidence: 99%